PERANCANGAN MESIN ES BALOK BERSUMBER LISTRIK TENAGA MATAHARI DI DESA MUNTAI KABUPATEN BENGKALIS - Hasibuan, Fardin; Wajhi Akramunnas, Bastul; Widagdo, Trijaya (SIGMA TEKNIKA, 2023)
fish is a food necessity as a source of protein for human life. Muntai Village in the Bantan District of Bengkalis Regency, Riau Province, is an area located on the Malacca Strait coast. Most of the village's population work as fishermen, both in saltwater and freshwater fishing. The primary production of fishermen is fish caught from the sea. The production of sea fish catches in the Bantan District in 2021 was 101 tons. Ice blocks are one of the components needed by the fishermen in Muntai Village. The distance from the village to the town, which takes around 1 to 1.5 hours, is a constraint in providing ice blocks for the fishermen in the village. The lack of electricity installation reaching the coastal area where the fishermen dock their boats is also one of the obstacles in providing ice blocks. The plan to create a solar-powered ice block machine is one of the alternative solutions to address the ice block supply issue for the fishermen in Muntai Village. The design of the ice block machine has a capacity of 3 tons per 24 hours with a power requirement of 13 kW and is sourced from solar panels with a specific number of solar cell modules. The investment cost required is Rp 833,051,670.00